Spiegare il ragionamento.
Spiegare il ragionamento.
1/(x^3 + 2·x^2 + x + 2) = 1/((x + 2)·(x^2 + 1))
poniamo:
1/((x + 2)·(x^2 + 1)) = (Α·x + Β)/(x^2 + 1) + C/(x + 2)=
= (x^2·(c + Α) + x·(2·Α + Β) + c + 2·Β)/((x + 2)·(x^2 + 1))
Risolviamo:
{Α + C = 0
{2·Α + Β = 0
{C + 2·Β = 1
ottenendo: C = 1/5 ∧ Α = - 1/5 ∧ Β = 2/5
1/((x + 2)·(x^2 + 1)) =
=((- 1/5)·x + 2/5)/(x^2 + 1) + 1/5/(x + 2)
1/((x + 2)·(x^2 + 1)) =
=(2 - x)/(5·(x^2 + 1)) + 1/(5·(x + 2))
∫((2 - x)/(5·(x^2 + 1))) dx=
=2·ATAN(x)/5 - LN(x^2 + 1)/10
∫(1/(5·(x + 2))) dx =
=LN(x + 2)/5
L'integrale indefinito è:
2·ATAN(x)/5 - LN(x^2 + 1)/10 + LN(x + 2)/5
Valutato in x = 1
2·ATAN(1)/5 - LN(1^2 + 1)/10 + LN(1 + 2)/5=
=LN(9/2)/10 + pi/10
valutato in x = 0
2·ATAN(0)/5 - LN(0^2 + 1)/10 + LN(0 + 2)/5= LN(2)/5
Quindi l'integrale dato vale:
LN(9/2)/10 + pi/10 - LN(2)/5 = LN(9/8)/10 + pi/10